2022
DOI: 10.1371/journal.pntd.0010812
|View full text |Cite
|
Sign up to set email alerts
|

The global trends and regional differences in incidence of Zika virus infection and implications for Zika virus infection prevention

Abstract: Background Zika virus (ZIKV) infection has potential result in severe birth effects. An improved understanding of global trend and regional differences is needed. Methods Annual ZIKV infection episodes and incidence rates were collected from Global Burden of Disease Study 2019. Episodes changes and estimated annual percentage changes (EAPCs) of age-standardized incidence rate (ASR) were calculated. Top passenger airport-pairs were obtained from the International Air Transport Association to understand places… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Although the number of disease cases caused by ZIKV has decreased in recent years, the virus is still circulating at low levels, causing disease, and it is also spreading to new areas around the world [ 39 ]. In a recent study of the cumulative global ZIKV burden since 2015, ZIKV infections demonstrated an increasing trend from 2011 to 2015, followed by a decreasing trend [ 40 ]. Importantly, when events occur, women between the ages of 15 and 49 are most affected.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of disease cases caused by ZIKV has decreased in recent years, the virus is still circulating at low levels, causing disease, and it is also spreading to new areas around the world [ 39 ]. In a recent study of the cumulative global ZIKV burden since 2015, ZIKV infections demonstrated an increasing trend from 2011 to 2015, followed by a decreasing trend [ 40 ]. Importantly, when events occur, women between the ages of 15 and 49 are most affected.…”
Section: Discussionmentioning
confidence: 99%
“…Вирусные инфекции признаны одним из глобальных вызовов в сфере биологической безопасности, требующих поиска современных решений по удовлетворению сохраняющейся потребности в эффективных и безопасных противовирусных препаратах: при существующем многообразии вирусных угроз, одобренные фармацевтические лекарственные средства прямого противовирусного действия доступны для лечения лишь 10 из указанных вирусных инфекций [1,2].…”
Section: Introductionunclassified
“…In 2007 a small outbreak of Zika fever was reported in the Yap Islands of Micronesia [5], followed a few years later by a larger outbreak in French Polynesia [6]. The outbreak in French Polynesia marked the start of the worldwide spread of the Asian lineage of ZIKV [3], and as of February 2022 the World Health Organization has reported 89 countries and territories as having ZIKV transmission, and transmission is still ongoing [7].…”
Section: Introductionmentioning
confidence: 99%